The Influence of Parental Guidance on Children's Religious Character - Anjani, Huly Luthfi Selfia; Istihana, Istihana; Susanti, Agus; Mustofa, Muhammad; Hijriyyah, Umi (International Journal on Advanced Science, Education, and Religion, 2025)
Parental guidance plays a very important role in the formation of children's character, especially in building religious character. In some cases, many parents do not understand or do not pay enough attention to this aspect, so that their children do not have a strong religious foundation. The purpose of this study was to determine the effect of parental guidance on children's religious character. This study uses a quantitative research type. The population in this study was 112 children in Bandar Jaya Timur Village, Terbanggi Besar District, Central Lampung Regency. Research sample. The research sample using the Slovin formula obtained 53 research samples. The results of the study based on a significance value of 0.006 <0.05, then Ha is accepted and Ho is rejected. It can be said that there is an influence of parental guidance on children's religious character.